Mutilating Procedures, Management Practices, and Housing Conditions That May Affect the Welfare of Farm Animals: Implications for Welfare Research - Nordquist, Rebecca E. (Animals (Basel), 2017)
SIMPLE SUMMARY: Intensive farming systems are confronted with a number of animal welfare issues such as injuries from horns in cattle and feather pecking in poultry. To solve these problems, mutilating procedures, such as dehorning in cattle and goats and beak trimming in laying hens, are applied routinely. These and other procedures such as early maternal separation, overcrowding, and barren housing conditions impair animal welfare. Scientific underpinning of the efficacy of these interventions and management practices is poor. We advocate that all stakeholders, in particular animal scientists and veterinarians, take the lead in evaluating common, putative mutilating and welfare reducing procedures and management practices to develop better, scientifically supported alternatives, focused on adaptation of the environment to the animals, to ensure uncompromised animal welfare. ABSTRACT: A number of mutilating procedures, such as dehorning in cattle and goats and beak trimming in laying hens, are common in farm animal husbandry systems in an attempt to prevent or solve problems, such as injuries from horns or feather pecking. These procedures and other practices, such as early maternal separation, overcrowding, and barren housing conditions, raise concerns about animal welfare. Efforts to ensure or improve animal welfare involve adapting the animal to its environment, i.e., by selective breeding (e.g., by selecting “robust” animals) adapting the environment to the animal (e.g., by developing social housing systems in which aggressive encounters are reduced to a minimum), or both. We propose adapting the environment to the animals by improving management practices and housing conditions, and by abandoning mutilating procedures. This approach requires the active involvement of all stakeholders: veterinarians and animal scientists, the industrial farming sector, the food processing and supply chain, and consumers of animal-derived products. Although scientific evidence about the welfare effects of current practices in farming such as mutilating procedures, management practices, and housing conditions is steadily growing, the gain in knowledge needs a boost through more scientific research. Considering the huge number of animals whose welfare is affected, all possible effort must be made to improve their welfare as quickly as possible in order to ban welfare-compromising procedures and practices as soon as possible.